RAPID DIAGNOSTIC DETECTION OF MALARIA PARASITES AMONG PRIMARY SCHOOL PUPILS OF AJIYOLO VILLAGE, DEKINA LOCAL GOVERNMENT AREA, KOGI STATE, NIGERIA - Amana, Gabriel Unekwu; Yaro, Clement Ameh; Afia, Udeme Udo; Idakwo, Joshua; Ocheje, Lucky Enemona (FUDMA Journal of Sciences, 2020)
An epidemiological study of malaria prevalence carried out in Ajiyolo community of Dekina Local Government Area of Kogi State, Nigeria. Blood samples were obtained from 214 consented asymptomatic participants from two (2) Primary Schools in Ajiyolo community. Rapid Diagnostic Test kits were used to detect malaria parasites in the blood. From the 214 participants examined, 80 (37.38%) were positive with malaria parasites. The group under age ten (U10) years had the highest malaria prevalence of 50.0% than the age-group of above ten (A10) with prevalence of 29.55%. The females (37.50%) had a higher prevalence than males (37.27%). There is no significant difference in prevalence between male and female, and also between males and females aged below 10 and above 10. The study has revealed that malaria disease can affect all age groups and both males and females’ sexes. Due to the high prevalence of asymptomatic malaria in this area, public enlightenment efforts need to be intensified towards the prevention of malaria, future interventions should be directed toward controlling malaria; thus, large-scale distribution of insecticide-treated nets or use of indoor residual spraying should be encouraged, and school aged children should be screen for malaria at interval, curative and prophylactic dose should be administered to pupils.